2015
DOI: 10.1115/1.4028676
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effect of a Realistic Flow Field on the Adiabatic Effectiveness of an Effusion-Cooled Combustor

Abstract: Effusion cooling represents the state of the art of liner cooling technology for modern combustors. This technique consists of an array of closely spaced discrete film cooling holes and contributes to lower the metal temperature by the combined protective effect of coolant film and heat removal through forced convection inside each hole. Despite many efforts reported in literature to characterize the cooling performance of these devices, detailed analyses of the mixing process between coolant and hot gas are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Numerical investigations have been widely conducted from various perspectives (Xia et al, 1998;Spencer et al, 2008;Xiao and Zheng, 2014;Andrei et al, 2015). Although the numerical results revealed valuable threedimensional mechanism of swirling flow to some degree, it was found that the numerical results weren't always satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations have been widely conducted from various perspectives (Xia et al, 1998;Spencer et al, 2008;Xiao and Zheng, 2014;Andrei et al, 2015). Although the numerical results revealed valuable threedimensional mechanism of swirling flow to some degree, it was found that the numerical results weren't always satisfactory.…”
Section: Introductionmentioning
confidence: 99%